Systematic design and analysis of solar thermal cooling systems in different climates. (August 2015) - Eicker, Ursula; Pietruschka, Dirk; Haag, Maximilian; Schmitt, Andreas
Abstract: About 1000 solar thermal cooling systems have been installed worldwide, so experience with system sizing and design is limited. To counter the lack of experience and to evaluate the potential of energy and cost efficient solar cooling systems, a systematic system design study has been carried out covering most climatic regions worldwide. For each technology investigated, an energy optimized control strategy was developed which maximizes the primary energy efficiency. It could be shown that a reduction of nominal chiller power by 30%–40% or more hardly affects the solar cooling fraction for most climates, but significantly increases the machine operating hours and thus improves the economics. Single effect absorption cooling systems easily reach 80% solar cooling fraction for all but very humid climates. Primary energy ratios can be over 3.0 and primary energy savings between 30 and 79%, depending on system design and cooling load data. The economic analysis shows that solar thermal cooling and heating is more viable in hot climates than in moderate European climates. To achieve payback times of 10 years with today's energy prices, the investment costs have to be reduced by 30–70% depending on the location and dimensioning. Highlights: Systematic energy and cost analysis of solar thermal cooling worldwide. Reduction of chiller size possible without loss of solar fraction. Payback in 10 years possible with 20–80% less investment costs.